(untitled) (Acta Scientiarum. Health Sciences, 2023)
This study aimed to evaluate the time between hospitalization and death of patients affected by COVID-19, and to investigate which factors are associated with this survival time. The data were obtained from the Influenza Epidemiological Surveillance Information System, which contains all cases of hospitalization for Severe Acute Respiratory Syndrome in Brazil. Initially, survival time was evaluated descriptively using the Kaplan-Meier estimator, which allows you to calculate the median survival time and the probability that a patient will survive certain periods of hospitalization. Next, a parametric regression model was constructed to investigate the relationship between the survival time and several factors jointly and the results were interpreted in terms of median survival time. Among the possible associated factors, the registration variables (gender, age, region, race and education), comorbidities and symptoms presented were considered. The results showed that the probability of a patient surviving the first day of hospitalization is 97.9%, dropping to 87.5% on the seventh day and reaching 33.5% on the thirtieth day. Half of the deaths occurred within 21 days of hospitalization and only 25% of the patients survived for more than 38 days, showing that, over time, the mortality rate decreases. Evaluating the associated factors, the results showed that elderly patients with low education have a shorter survival time and, consequently, a higher risk of death. With regard to comorbidities, neurological and liver diseases are the main risk factors. On the other hand, we do not have enough evidence to state that survival time is influenced by puerperal variables, down syndrome and abdominal pain.